1994
DOI: 10.1111/j.1530-0277.1994.tb01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Alcohol Involvement in Trauma Patients: Search for a Surrogate

Abstract: This study explores the potential for the development of a surrogate for alcohol-involved traumatic injury. It presents a bivariate probit analysis that simultaneously models likelihoods of patients being tested for blood alcohol content (BAC) and having positive BACs given testing using 17,356 adult trauma cases selected from the California Regional Trauma Registry. It concludes that patient and injury characteristics predict both testing and BAC, and that a weighting scheme may be profitably used to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…For example, we found that when alcohol and/or drug use was unknown in both T&H and TCO patients, these models estimated the number of cases that involved alcohol and/or drugs at levels similar to those actually seen in each center/facility group. These findings are consistent with the prior California research [7,8], and indicate that the alcohol/ drug models in this study offer a viable option for estimating alcohol and/or drug involvement in assault injuries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, we found that when alcohol and/or drug use was unknown in both T&H and TCO patients, these models estimated the number of cases that involved alcohol and/or drugs at levels similar to those actually seen in each center/facility group. These findings are consistent with the prior California research [7,8], and indicate that the alcohol/ drug models in this study offer a viable option for estimating alcohol and/or drug involvement in assault injuries.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, given that hospital discharge records usually do not contain illicit substance information, it is often difficult to assess the impact of such substances on intentional injuries. Prior research in California has demonstrated that if data were available for a subset of traumatic assault cases, then substance use in the remaining cases can be estimated [7,8].…”
mentioning
confidence: 99%
“…It has been shown that intoxicated patients have a greater base deficit because of a metabolic acidosis that is independent of injury severity. 18,22,23 It is plausible that more aggressive resuscitation in the intoxicated group based on a greater base deficit could result in the differences in survival shown, but more likely, the difference in survival is because of differences in TBI severity between the two groups. Nonintoxicated patients were more likely to have more severe head injuries based on head AIS.…”
Section: Discussionmentioning
confidence: 95%
“…A considerable proportion of presentations at hospital emergency departments are alcohol related (Cherpital, 1993). The proportion with alcohol involvement also increases markedly during late evening/ early morning, and in most settings alcohol-related presentations are concentrated on weekend nights (Hulse, Robertson, & Tait, 2001;McLeod, Stockwell, Stevens, & Phillips, 1999;Treno, Cooper, & Roeper, 1994). Discussions with local service agencies indicated, however, that drinking in both locations was spread through the week.…”
Section: Serial Measures Of Alcohol Consumption and Harmmentioning
confidence: 93%